The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jfd.12825
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic characterization of Hysterothylacium Ward & Magath, 1917 (Nematoda: Raphidascarididae) larvae in horse mackerel, blue whiting and anchovy from Spanish Atlantic and Mediterranean waters

Abstract: The presence of zoonotic Hysterothylacium larvae in fish from Spanish Atlantic and Mediterranean waters, which can cause economic losses for commercial fisheries, has been reported in several studies; however, little is known about species identity in this region. The aim of this study was to identify at species level the Hysterothylacium morphotypes detected in three commonly consumed fish: horse mackerel (Trachurus trachurus), blue whiting (Micromesistius poutassou) and anchovy (Engraulis encrasicolus). Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The nematode Hysterothylacium sp. (mainly H. aduncum), a member of the Raphidascarididae family, is a common parasite of marine fish throughout the world (Andersen, 1993;Rello et al, 2008;Knoff et al, 2012;Moravec et al, 2012;Kong et al, 2015;Morsy et al, 2015;Shamsi et al, 2015;Shamsi et al, 2016;Shamsi, 2017;Ghadam et al, 2018;Roca-Geronès et al, 2018) and is the most frequently occurring parasite in invertebrates acting as intermediate hosts: it has been reported in 70 different invertebrate species (Lick, 1991). Hysterothylacium aduncum (Rudolphi 1802) has a circumpolar distribution in the Northern hemisphere (Deardorff and Overstreet, 1981) and has been found in the north-west Atlantic (Marcogliese, 1996), the North Sea and the Baltic Sea (Lick, 1991;Klimpel and Ruckert, 2005), but also in the Mediterranean Sea (Dural et al, 2011;Abdel-Ghaffar et al, 2015), the Black Sea (Pekmezci et al, 2013) and the waters around Japan (Moravec and Nagasawa, 1986;Kong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The nematode Hysterothylacium sp. (mainly H. aduncum), a member of the Raphidascarididae family, is a common parasite of marine fish throughout the world (Andersen, 1993;Rello et al, 2008;Knoff et al, 2012;Moravec et al, 2012;Kong et al, 2015;Morsy et al, 2015;Shamsi et al, 2015;Shamsi et al, 2016;Shamsi, 2017;Ghadam et al, 2018;Roca-Geronès et al, 2018) and is the most frequently occurring parasite in invertebrates acting as intermediate hosts: it has been reported in 70 different invertebrate species (Lick, 1991). Hysterothylacium aduncum (Rudolphi 1802) has a circumpolar distribution in the Northern hemisphere (Deardorff and Overstreet, 1981) and has been found in the north-west Atlantic (Marcogliese, 1996), the North Sea and the Baltic Sea (Lick, 1991;Klimpel and Ruckert, 2005), but also in the Mediterranean Sea (Dural et al, 2011;Abdel-Ghaffar et al, 2015), the Black Sea (Pekmezci et al, 2013) and the waters around Japan (Moravec and Nagasawa, 1986;Kong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence in Spain can be chiefly attributed to the country's culinary traditions, with most infections deriving from the popular consumption of European anchovies (Engraulis encrasicolus) and European pilchard (Sardina pilchardus), marinated in vinegar [2,22]. Other fish which are widely consumed in Spain include blue whiting (Micromesistius poutassou), horse mackerel (Trachurus trachurus), European hake (Merluccius merluccius), and Atlantic bonito (Sarda sarda), and these present high infection rates for ascaridoid larvae [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Species of the genus Hysterothylacium Ward and Magath, 1917, formerly belonging to the Anisakidae and currently assigned to the family Raphidascarididae, are common parasites in different marine and freshwater fish species (Bezerra et al 2020 ). H. aduncum Rudolphi, 1802 and H. fabri Rudolphi, 1819 are the most frequently reported species in teleost fish from the Mediterranean region (Roca‐Geronès et al 2018 ; Tedesco et al 2018 ). Evidence of the direct consequences of Hysterothylacium infection on fish health is limited: parasites of this genus are considered only mildly pathogenic for adult fish (Ishikura et al 1993 ; Yagi et al 1996 ; Valero et al 2003 ; Cavallero et al 2012 ); however, mortality episodes in larval and juvenile fish have been reported (Bristow 1990 ; Balbuena et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%